2015
DOI: 10.1063/1.4905585
|View full text |Cite
|
Sign up to set email alerts
|

Defect-band mediated ferromagnetism in Gd-doped ZnO thin films

Abstract: Defect-band mediated ferromagnetism in Gd-doped ZnO thin films Gd-doped ZnO thin films prepared by pulsed laser deposition with Gd concentrations varying from 0.02-0.45 atomic percent (at. %) showed deposition oxygen pressure controlled ferromagnetism. Thin films prepared with Gd dopant levels ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 45 publications
(42 reference statements)
3
17
0
2
Order By: Relevance
“…The exchange interaction is therefore dependent on the Gd concentration. Subramanian et al [16] observed anisotropy in polycrystalline Gd-doped ZnO [23].…”
Section: The Effect Of Oxygen Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange interaction is therefore dependent on the Gd concentration. Subramanian et al [16] observed anisotropy in polycrystalline Gd-doped ZnO [23].…”
Section: The Effect Of Oxygen Deficiencymentioning
confidence: 99%
“…In this case, the band broadening formed by intrinsic defects is resonant with Gd f states producing RTFM [52], as shown in Figure 13. Venkatesh et al [23] showed that the formation of a Gdoxygen-deficiency defect band located near the Fermi level mediated the ferromagnetism through spin splitting of the defect band [22].…”
Section: The Origin Of the Ferromagnetism In Gd-doped Zno Filmsmentioning
confidence: 99%
“…Near edge X-ray absorption fine structure spectra at the O K-edge and Gd M5,4-edges indicated that Gd atoms replace Zn sites. 38,63 Therefore, the incorporation of Gd dopants creates a donor band below the conduction band maximum. Due to the donor band created near the CBM, a shift in the Fermi level occurs, and the material Please do not adjust margins Please do not adjust margins conductivity increases.…”
Section: Growth Mechanismmentioning
confidence: 99%
“…In addition, Gddoped/implanted ZnO exhibited room temperature (RT) ferromagnetic behavior that has been attributed to defect/impurity bands mediated by Gd dopants. [7][8][9][10][11][12] Another interesting phenomenon that has been observed in Gd-doped ZnO is a Kondo-like effect, occurring due to a coupling between carriers and localized spin. 13 More specifically, the electrostatic tuning of Kondo effect in Gd-doped ZnO was demonstrated for electrical-double layer transistor applications.…”
Section: Introductionmentioning
confidence: 99%